Kebijakan Relokasi Pasar dan Dampaknya terhadap Pendapatan Pedagang (Studi Pada: Pasar Bauntung Baru Banjarbaru) - Salsabila, Namira; Wardhana, Ali (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine the process of planning the relocation policy of Bauntung Market to Bauntung Baru Market and to determine the impact on the income of traders after being relocated. This research was conducted in Banjarbaru City, precisely in Bauntung Baru Market, using primary data from questionnaires that the respondents had filled out. Respondents are Bauntung Baru Market Traders. This study uses a qualitative descriptive analysis technique. The results of this study indicate that the new Bauntung market relocation policy was carried out because the old Bauntung market was not adequate regarding traders and land area. The impact of this relocation policy for traders is that most of their income has decreased from before the relocation.